Complex Regional Pain Syndrome: Practical Diagnostic and Treatment Guidelines, 4th Edition. Issue 2 (17th January 2013) - Harden, R. Norman; Oaklander, Ann Louise; Burton, Allen W.; Perez, Roberto S. G. M.; Richardson, Kathryn; Swan, Melanie; Barthel, Jennifer; Costa, Brienne; Graciosa, Joseph R.; Bruehl, Stephen
Abstract Objective This is the fourth edition of diagnostic and treatment guidelines for complex regional pain syndrome (CRPS; aka reflex sympathetic dystrophy). Methods Expert practitioners in each discipline traditionally utilized in the treatment of CRPS systematically reviewed the available and relevant literature; due to the paucity of levels 1 and 2 studies, less rigorous, preliminary research reports were included. The literature review was supplemented with knowledge gained from extensive empirical clinical experience, particularly in areas where high‐quality evidence to guide therapy is lacking. Results The research quality, clinical relevance, and "state of the art" of diagnostic criteria or treatment modalities are discussed, sometimes in considerable detail with an eye to the expert practitioner in each therapeutic area. Levels of evidence are mentioned when available, so that the practitioner can better assess and analyze the modality under discussion, and if desired, to personally consider the citations. Tables provide details on characteristics of studies in different subject domains described in the literature. Conclusions In the humanitarian spirit of making the most of all current thinking in the area, balanced by a careful case‐by‐case analysis of the risk/cost vs benefit analysis, the authors offer these "practical" guidelines.